Do aquatic macrophytes configuration mode impact water quality? - Wang, Hui-Hui; Liu, Jing-Lan; Zhang, Rong; Liu, Jia-Kai; Zou, Yu-Qi; Zhang, Zhen-Ming (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper had selected watermifoil (Myriophyllum veticillatum Linn.), softstem bulrush (Scirpus validus Vahl) and yellow-flowered iris (Iris wilsonii), in showing the water purification through different configuration. AFIs with different combination of aquatic plants were set up to purify the water quality for 50 days. This paper aimed to evaluate chemical and vegetative characteristics of each type of plant and also to find configuration of aquatic plants to maximize the contaminants removal efficiency by artificial floating island (AFI). The result indicated that the trophic waterbody promote the growth of plants and all of the AFIs have the ability to purify water and reduce contaminants. However, the most effective way is by combination of these three aquatic plants which has strong capacity to remove COD, NO3-, total nitrogen, total phosphorous and improve pH levels. Watermifoil (Myriophyllum verticillatum Linn.) is better than yellow-flowered iris (Iris wilsonii) and softstem bulrush (Scirpus validus Vahl) in disposing water pollutants.